-3(-8v+8)-4=36+8v

Simple and best practice solution for -3(-8v+8)-4=36+8v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(-8v+8)-4=36+8v equation:


-3(-8v+8)-4=36+8v

We simplify the equation to the form, which is simple to understand
-3(-8v+8)-4=36+8v

Reorder the terms in parentheses
+(+24v-24)-4=36+8v

Remove unnecessary parentheses
+24v-24-4=+36+8v

We move all terms containing v to the left and all other terms to the right.
+24v-8v=+36+24+4

We simplify left and right side of the equation.
+16v=+64

We divide both sides of the equation by 16 to get v.
v=4

See similar equations:

| -3f+(-6)=-105 | | 21x=-6 | | 29+x=-6-7(3x-5) | | 3x+35=11x-7 | | x/8+6 | | 3x^2-24-1x=0 | | -1+x/-3=4 | | -13m+7m=16-52 | | -5v-(-24)=-106 | | X/9+5=13 | | 69=3(-8k-1) | | 9/5(240-273.15)+32 | | 9m-23=-572 | | -4a-46=98 | | 15a+24=39 | | -10=x/9+16 | | 81=2(-5+7n)-n | | -6k+78=6 | | 8e+29=-83 | | 8t=10 | | 6t+3t=4-7+21 | | 0.03r+52.3=52.447 | | .02(6t-3)=.12(t-2)+.18 | | 3(2y+7)-y=11 | | 0.35/0.0084 | | -6(3x-3)=-(5x+2) | | -77=7y+35 | | .007a-.012=.0153 | | 0.8w-3.2=2.48 | | x-(12-4x)=-2(5-3x)+4 | | -38-4n=-5(n+7) | | -281.05=12.5k+10.2 |

Equations solver categories